Godspeed : a novel - Butler, Nickolas (G.P. Putnam's Sons, 2021)
"In this riveting new novel by the bestselling and award-winning author of Shotgun Lovesongs, three troubled construction workers get entangled in a dangerous plan to finish building a home against an impossible deadline"--